KARAKTERISTIK MORFOLOGI DAN ANATOMI TANAMAN MANGGIS (Garcinia mangostana L.) DI DESA BATUSUYA DAN LABEAN KABUPATEN DONGGALA - Alqadri, Alqadri; Tambing, Yohanis; Latarang, Burhanudin (AGROTEKBIS, 2016)
This study aims to identify the morphology and anatomy of mangosteen in Donggala especially in the Village Labean and Batusuya. Collection of material using morphological methods of exploration in the field of mangosteen in the Village and Village Batusuya Labean, while observing the anatomy of mangosteen conducted at the Laboratory of Integrated Pest and Disease Tadulako. The research was conducted from August to October 2015. The total sample of mangosteen were observed for morphology and anatomy is 20 samples consisted of 10 samples from the Village Batusuya and 10 samples from the Village Labean, the collected data were analyzed using cluster analysis and the results are seen in dendogram form. From the results contained dendogram diverse accessions of mangosteen in Donggala, especially in the Village and Village Batusuya Labean. Of the existing diversity obtained by the two groups in the Village Batusuya namely BS1 and BS4. Likewise the two groups for the Village Labean ie LB4 and LB2. And a combination of two villages in the two groups obtained mangis namely BS4 and LB2.Â Key Words: Anatomy, mangosteen, morphology.Â